Knowledge of 16-21 year old adolescents living in Barangay UP Campus on the possible consequences of sexual intercourse - Calaguas, Meryl Joy C.; Belmonte, Karla Karina A.; De Leon, Ma. Perlita (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The study's aim was to describe the knowledge of 16-21 year old adolescents from Barangay UP Campus on the topics of possible consequences of sexual intercourse, specifically HIV/AIDS and early pregnancy. Data was gathered from 104 adolescent males and females living in selected areas of Barangay UP Campus through a survey called The Knowledge of Possible Consequences of Sexual Intercourse Test specifically designed by the researchers for this study. It was followed by an interview of ten respondents to identify their sources of information on sexual intercourse and its possible consequences. The survey scores of the male and female respondents were later compared. Results showed the adolescents' familiarity with concepts on the topics, the main sources of information being friends and web sources and with female respondents scoring higher than males. The study encourages continued research on sex education as well as education of adolescents and their parents on the possible negative consequences of sexual intercourse at a very young age.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Teenagers -- Philippines; Sexual intercourse